Evidence-based medicine databases: An overview - Viji Pulikkel Chandran, Sohil Khan, Girish Pai Kulyadi, Kanav Khera, Elsa Sanatombi Devi, Athira Balakrishnan, Girish Thunga (Journal of Applied Pharmaceutical Science, 2020)
Evidence-based medicine (EBM) helps to bridge the gap between current healthcare practice and recent research findings in health care. Today’s era of scientific information explosion makes hard for healthcare providers to remain up to date on the best clinical practices. In reality, a physician has to read 17 scientific literature works per day to remain up to date. This is a difficult challenge, but EBM databases provide quick access to research findings. This review aims to provide an overview of EBM databases. These databases provide information about guidelines, disease, treatment, diagnosis, clinical relevance, systematic reviews, clinical trials, observational studies, preappraised information, summary, abstract, full text, similar studies, short reports, clinical queries, images, e-textbooks, patient counseling information, and continuous medical education in a minimum period of time. The identification and utilization of recent research findings is a critical step to enhance patient care and clinical practice. This review provides an insight into various EBM databases, type of evidence, access details, and link to each database. Establishing educational requirements and awareness in the practice of EBM among healthcare professionals is a great step for promoting the practice of EBM.
Keywords: Evidence-based medicine, evidence-based practice, EBM databases, learning.